(untitled) - MASLACHAH, MALA (RETAIN : Journal of Research in English Language Teaching, 2014)
Abstrak Speaking is one of important skill that should be mastered by students who learn English. The aim of teaching speaking is students are able to use the language in real communication situation. Moreover, speaking is known as the most difficult skill because the spelling and the pronunciation are different. Here, the teacher is needed to maintain student’s motivation in order to keep students’ interest in speaking. Video is media of communication which contains some information. Furthermore, authentic video is any material which is bought, recorded from television. Meanwhile, made for language teaching video is any kind of video that is designed for learning the target language. The examples of authentic video are feature films (fiction), cartoons, documentaries, news, interviews, game shows, and advertisements or commercials. This is a descriptive qualitative research and this research is aiming to describe the implementation of short animated folktale video in teaching speaking narrative. The data are obtained from checklist, field note, questionnaire, and also students’ task. The researcher endeavored to record the implementation of short animated video in teaching speaking narrative and describe it. The description is explained based on three objectives of the study. Those are the implementation of short animated folktale video to teach speaking narrative, the students’ speaking task result, and also students’ responses toward the implementation of short animated folktale video in speaking narrative. After observing, the researcher described three results. The first result was regarding the implementation of short animated folktale video applied. There are three steps how the teacher applied. They were pre-viewing activity, viewing activity, and post-viewing activity. The second result was the students’ responses toward the implementation of short animated folktale video. They students gave positive responses and they agreed if the video was used in teaching-learning process. And the last finding was the students’ speaking skill by using FSI rubric by Oller. It has five components in speaking. They are pronunciation, grammar, vocabulary, fluency, and comprehension. It was proved that the students speaking ability got better after studying speaking narrative using animated folktale video.In conclusion, the animated folktale video could be used to teach speaking narrative, particularly for tenth grade students. It could be even used to keep students’ willingness in speaking because of their interest in the story of the animated folktale video. Kata Kunci: animated folktale video, speaking, narrative, students’ response.